Emotional blunting with antidepressant treatments: A survey among depressed patients - Goodwin, G; Price, J; De Bodinat, C; Laredo, J (Elsevier, 2017)
Emotional blunting is regularly reported in depressed patients on antidepressant treatment but its actual frequency is poorly understood. We have previously used qualitative methods to develop an appropriate scale, the Oxford Questionnaire on the Emotional Side-Effects of Antidepressants (OQESA).Six hundred and sixty nine depressed patients on treatment and 150 recovered (formerly depressed) controls (aged ≥18 years) participated in this internet-based survey. The rate of emotional blunting in treated depressed patients was 46%, slightly more frequent in men than women (52% versus 44%) and in those with higher Hospital Anxiety and Depression (HAD) scale scores. There was no difference according to antidepressant agent, though it appeared less frequent with bupropion. Depressed patients with emotional blunting had much higher total blunting scores on OQESA than controls (42.83 ± 14.73 versus 25.73 ± 15.00, p < 0.0001) and there was a correlation between total blunting score and HAD-Depression score (r = 0.521). Thus, those with HAD-D score >7 (n = 170) had a higher total questionnaire score, 49.23±12.03, than those with HAD-D score ≤7 (n = 140), 35.07 ± 13.98, and the difference between the two groups was highly significant. However, patients with HAD-D score ≤7 (n = 140) had a higher total score (35.07 ± 13.98) than the recovered controls (n = 150) (25.73 ± 15.00), and the difference between the two groups was significant. Among the patients with emotional blunting, 37% had a negative perception of their condition and 38% positive. Men reported a more negative perception than women (p=0.008), and patients with a negative perception were more likely to have higher HAD scores. Higher levels of emotional blunting are associated with a more negative perception of it by the patient (r = -0.423).Include self-evaluation and the modest size of the sample for detection of differences between antidepressants.Emotional blunting is reported by nearly half of depressed patients on antidepressants. It appears to be common to all monoaminergic antidepressants. The OQESA scores are highly correlated with HAD depression score; emotional blunting cannot be described simply as a side-effect of antidepressants, but also as a symptom of depression. A higher degree of emotional blunting is associated with a poorer quality of remission. The OQESA scale allows the detection of this phenomenon.